STUDY OF CONSUMER ACCEPTANCE ON MACKEREL (Rastrelligerkanagurta) SHREDDED WITH ADDITION DIFFERENT AMOUNT OF BANANA BLOSSOM (Musa paradisiaca) - Irsan Taufik; Suparmi Suparmi; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study was aimed to determine the level of consumer acceptance onshredded mackerelwith the addition ofbanana blossom consist of 4 treatment levels A0 (control), A1 (30% of banana blossom), A2 (50% of banana blossom), and A3 (70% of banana blossom) with 3 replicated, so there were 12 units of experimental units. Based on the results showed thatthe addition of banana blossom to the production of shreddedmackerel had a very significant effect on the value of appearance, odor, flavor, and texture.The A1 treatment (addition 30% of banana blossom) was the best treatment withthe characteristics rather golden yellow color (3.68), seasoning aroma and specific odor of fish meat (3.61), the flavor of the seasoning was as specific as the taste of the fish meat(3.64), and chewy texture and little compact (3.75). Meanwhile for proximate analysis of A1 treatment of moisture, protein, fat, ash, and fiber content was 27.23%, 33.55%, 22.08%, 6.78%, and 1.59%, respectively.Keywords:banana bud, mackerel shredded,organoleptic, proximate,Rastrelliger